Pengaruh Flash Sale dan Free Shipping terhadap Impulsive Buying Behavior dalam Perspektif Ekonomi Islam - Imas Permatasari; Moh Mukhsin; Isti Nuzulul Atiah (OIKONOMIKA: Jurnal Kajian Ekonomi dan Keuangan Syariah, 2023)
This research was conducted to obtain scientific results related to the effect of flash sales and free shipping on impulsive buying behavior from the perspective of Islamic Economics in Islamic Economics Students at Sultan Ageng Tirtayasa University who are Shopee users. Quantitative methods are used to analyze primary data obtained from the results of distributing questionnaires. The sample was calculated based on the slovin formula, namely 62 Islamic Economics students from the 2019-2021 class. Data analysis used IBM SPSS 22. The results of the t-test showed that partially flash sales and free shipping had a positive and significant effect on impulsive buying behavior. The results of the F test showed that flash sales and free shipping simultaneously have a positive and significant effect on impulsive buying behavior. The results of the test for the coefficient of determination show that the contribution of flash sales and free shipping to impulsive buying behavior is 58.5%.